Design and implementation of single-phase hybrid active power filter controller - Rahim, N.A.; Mekhilef, Saad; Zahrul, I. (2005)
This paper presents a combination of a series active power filter and a shunt passive filter. The shunt passive filter is connected in parallel with a load and suppresses the harmonic current produced by the load, whereas the active filter connected in series to a source acts as a harmonic isolator between the source and load. For active filter control, Sinusoidal Pulse Width Modulation (SPWM) is developed and the modulation index is selected by calculating the DC bus voltage of the active filter. The PSpice®, Matlab/Simulink® and MAX PLUS II® softwares are used for simulation and hardware implementation. © 2005 IEEE.